Analysing Arguments in Networked Conversations: The Context of Student Teachers - Campos, Milton N.; LaFerriere, Therese; LaPointe, Judith M. (Canadian Journal of Higher Education, 2005)
The purpose of this article is to demonstrate how the method of meaning implication discourse analysis can be applied in the context of online collaborative reflective practice of student teachers. The method was developed to identify knowledge building in networked contexts. It derives from the model of meaning implication developed by Piaget, and the model of “schematization” proposed by Grize. It also borrows from the knowledge building theory developed by Scardamalia and Bereiter. The method allows understanding knowledge construction as an evolving process of conceptual change and learning through argumentation. We present two studies in which online “conversations” of pre-service teachers are analyzed. Contributions for higher education are discussed.